So You Want to Sing World Music: A Guide for Performers - Hoch, Matthew (Rowman & Littlefield Publishers, 2019)
In recent decades, world music styles have been making increasing inroads into Western popular music, music theater, choral concerts, and even concert hall performances. So You Want to Sing World Music is an essential compendium of these genres and provides technical approaches to singing non-Western styles. Matthew Hoch gathers a cohort of expert performers and teachers to address singing styles from across the globe, including Tuvan throat singing, Celtic pop and traditional Irish singing, South African choral singing, Brazilian popular music genres, Hindustani classical singing, Native American vocal music, Mexican mariachi, Lithuanian sutartinės, Georgian polyphony, Egyptian vocal music, Persian āvāz, and Peking opera. Additional chapters offer resources for soloists and choral directors as well as primers on voice science, vocal health, and audio enhancement technology. The So You Want to Sing series is produced in partnership with the National Association of Teachers of Singing. Like all books in the series, So You Want to Sing World Music features online supplemental material on the NATS website. Please visit www.nats.org to access style-specific exercises, audio and video files, and additional resources.